2024
DOI: 10.3390/educsci14010082
|View full text |Cite
|
Sign up to set email alerts
|

A Current Overview of the Use of Learning Analytics Dashboards

Italo Masiello,
Zeynab (Artemis) Mohseni,
Francis Palma
et al.

Abstract: The promise of Learning Analytics Dashboards in education is to collect, analyze, and visualize data with the ultimate ambition of improving students’ learning. Our overview of the latest systematic reviews on the topic shows a number of research trends: learning analytics research is growing rapidly; it brings to the front inequality and inclusiveness measures; it reveals an unclear path to data ownership and privacy; it provides predictions which are not clearly translated into pedagogical actions; and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
(245 reference statements)
0
4
0
2
Order By: Relevance
“…Узагальнено, що особливі освітні потреби в науковому середовищі охоплюють значний пласт змістових ознак з урахуванням зовнішніх чинників, в основному спровокованих нестандартними обставинами. Таке розуміння досліджуваного феномена визначає ставлення представників наукового співтовариства insight.stateuniversity.ks.ua ISSN 2663-970Х (Chen et al, 2023;Kononenko et al, 2020;Rice et al, 2023) and methods of communication and interaction (Kurova et al, 2023), on practices of self-efficacy formation in the leading activity of students and teachers (Celestino et al, 2024;Halian et al, 2023a;2023b), on taking into account the adaptation potential (Blynova et al, 2022;Nosov et al, 2020), on creating conditions for the implementation of acceptable forms of education and the use of health-preserving technologies, the implementation of mixed forms of education, as well as a pedagogical approach to ensure fairness and barrier-free access to information (Masiello et al, 2024) and educational services .…”
Section: On Taking Into Consideration Individual Typological Propertiesunclassified
See 1 more Smart Citation
“…Узагальнено, що особливі освітні потреби в науковому середовищі охоплюють значний пласт змістових ознак з урахуванням зовнішніх чинників, в основному спровокованих нестандартними обставинами. Таке розуміння досліджуваного феномена визначає ставлення представників наукового співтовариства insight.stateuniversity.ks.ua ISSN 2663-970Х (Chen et al, 2023;Kononenko et al, 2020;Rice et al, 2023) and methods of communication and interaction (Kurova et al, 2023), on practices of self-efficacy formation in the leading activity of students and teachers (Celestino et al, 2024;Halian et al, 2023a;2023b), on taking into account the adaptation potential (Blynova et al, 2022;Nosov et al, 2020), on creating conditions for the implementation of acceptable forms of education and the use of health-preserving technologies, the implementation of mixed forms of education, as well as a pedagogical approach to ensure fairness and barrier-free access to information (Masiello et al, 2024) and educational services .…”
Section: On Taking Into Consideration Individual Typological Propertiesunclassified
“…Adlet Kariyev Gulsim Lekerova Fauziya Orazbayeva до навчання в університеті, яке базується на акцентуванні уваги на саморегуляції (Prokhorenko et al, 2023) і самоактуалізації домінуючих психічних станів (Popovych et al, 2022), на врахуванні індивідуально-типологічних властивостей (Chen et al, 2023;Kononenko et al, 2020;Rice et al, 2023) і способів комунікації та взаємодії (Kurova et al, 2023), на практиках формування самоефективності у провідному виді діяльності здобувачів і викладачів (Celestino et al, 2024;Halian et al, 2023a;2023b), на врахуванні адаптаційного потенціалу (Blynova et al, 2022;Nosov et al, 2020), на створенні умов для реалізації прийнятних форм навчання і застосування здоров'язберігаючих технологій, імплементації змішаних форм навчання, а також педагогічного підходу для забезпечення справедливості і безбар'єрності доступу до інформації (Masiello et al, 2024) та освітніх сервісів .…”
Section: Marzhan Moldakhanovaunclassified
“…They list the techniques used in predictive analytics as '[d]ata visualisations via specific tools to provide program/degree level metrics on student enrolments, program stage, results and survey feedback to give teaching staff visual snapshots of students in their programs' (Society for Learning Analytics Research 2024). Masiello et al (2024) provide a current overview of the use of learning analytics dashboards (LADs), which they define as 'control panels that can be tailored to display LA components that update according to the learning processes, also in real time'. Visualisations 'mainly exemplify descriptive information, such as time spent on an online task, access to various online resources, and learning progression in a course or subject/task, but also to provide means to compare user results'.…”
Section: Learning Analytics and Documentationmentioning
confidence: 99%
“…Visualisations 'mainly exemplify descriptive information, such as time spent on an online task, access to various online resources, and learning progression in a course or subject/task, but also to provide means to compare user results'. Using an 'umbrella review' approach (Choi and Kang 2022), Masiello et al (2024) compile evidence from multiple systematic reviews on the use of LADs in education, posing the research question: 'What is the current use of learning analytics dashboards in education? ' Masiello et al (2024) found that the common visualisation techniques were 'graphs, such as line charts, bar charts, progress bars, pie charts, and timelines'.…”
Section: Learning Analytics and Documentationmentioning
confidence: 99%
See 1 more Smart Citation